Marley & me : life and love with the world's worst dog - Grogan, John. (New York : HarperCollins Publishers, 2005)
John and Jenny were just beginning their life together. They were young and in love, with not a care in the world. Then they brought home Marley, a wiggly yellow furball of a puppy. Life would never be the same. Marley grew into a barreling, ninety-seven-pound steamroller of a Labrador retriever. He crashed through screen doors, gouged through drywall, and stole women's undergarments. Obedience school did no good -- Marley was expelled. But just as Marley joyfully refused any limits on his behavior, his love and loyalty were boundless, too. Marley remained a model of devotion, even when his family was at its wit's end. Unconditional love, they would learn, comes in many forms. Marley & Me is John Grogan's funny, unforgettable tribute to this wonderful, wildly neurotic Lab and the meaning he brought to their lives.
1. And puppy makes three -- 2. Running with the blue bloods -- 3. Homeward bound -- 4. Mr. Wiggles -- 5. The test strip -- 6. Matters of the heart -- 7. Master and beast -- 8. A battle of wills -- 9. The stuff makes are made of -- 10. The luck of the Irish -- 11. The things he are -- 12. Welcome to the indigent ward -- 13. A scream in the night -- 14. An early arrival -- 15. A postpartum ultimatum -- 16. The audition -- 17. In the land of Bocahontas -- 18. Alfresco Dining -- 19. Lightning strikes -- 20. Dog beach -- 21. A northbound plane -- 22. In the land of pencils -- 23. Poultry on parade -- 24. The potty room -- 25. Beating the odds -- 26. Borrowed time -- 27. The big meadow -- 28. Beneath the cherry trees -- 29. The bad dog club.
Keywords: LABABRADORS FLORIDE -- HUMAN-ANIMAL RELATIONSHIP -- BIOGRAPHIES